The Evaluation Procedure of Educational Materials in Zambia and its Challenges. - Chavula, Jane (Advances in Social Sciences Research Journal, 2018)
This paper highlights the evaluation procedure of materials at the Curriculum Development Centre in Zambia based on lived experiences and literature review on the subject. The quality of education in Zambia has been demonstrated by low student achievement in national and international assessments. Many factors have contributed to undermining the standards and quality of education and one of the factors is a dearth of textbooks and other learning materials. Hence there is dependence on the materials available, therefore there is need to ensure that the materials which are used in schools are of high standards. The Ministry of Education, Science, Vocational Training and Early Education came up with the Evaluation Criteria to make sure that once materials are evaluated and approved or recommended then, they will be good enough for use in Schools. But this is not the case as some of the books found in schools are of low standards and with shallow content. This is so because some good evaluators shun evaluating materials because the payments involved are not attractive. Some publishers supply materials which have mistakes instead of printing the final copy which was approved. Therefore, there is need to strengthen the evaluation committees and to make follow-ups over the final copies being published by the publishers.